A Theoretical Approach to Financial Therapy: The Development of the Ford Financial Empowerment Model - Megan R Ford; Joyce A Baptist; Kristy L Archuleta (Journal of Financial Therapy, 2011)
The purpose of this paper is to introduce an integrative approach to working with clients experiencing problems related to financial disempowerment. The multi-phase model integrates three theoretically-driven psychotherapy approaches, including cognitive behavioral, narrative, and Virginia Satir’s experiential therapies, and financial counseling techniques to increase one’s sense of financial empowerment. A case study is included to demonstrate the applicability and effectiveness of the model.
Keywords: financial therapy; marriage and family therapy; financial counseling